Management of a Patient with Metabolic Dysfunction-Associated Steatotic Liver Disease and Periodontitis - Makovei, Yaroslav; Soloviova, Halyna; Trehubenko, Anhelina; Symonenko, Renata (The Ukrainian Scientific Medical Youth Journal, 2026)
Abstract. Introduction. Metabolic dysfunction-associated steatotic liver disease (MASLD) is currently recognized as a multicomponent systemic pathology extending far beyond isolated hepatobiliary impairment. MASLD serves as a hepatic manifestation of metabolic syndrome and is pathogenetically linked to an elevated risk of type 2 diabetes mellitus progression, abdominal obesity, atherogenic dyslipidemia, cardiovascular complications, and chronic low-grade systemic inflammation. The comorbid course of MASLD and generalized periodontitis is of particular clinical and scientific interest. Both pathological states share common pathogenetic pathways, where tissue insulin resistance, systemic oxidative stress, proinflammatory cytokine imbalance, endothelial dysfunction, and mutual aggravation due to the persistence of a chronic oral infection focus play a pivotal role. Aim. The aim of this study is to demonstrate the features of non-invasive diagnostics and multidisciplinary management in a young patient presenting with a combination of MASLD, type 2 diabetes mellitus, obesity, and chronic periodontitis. Materials and Methods. The article analyzes a clinical case of a 34-year-old patient S. referred by a dentist due to the aggressive course of periodontitis. Physical examination revealed signs of class I obesity. Laboratory monitoring demonstrated insulin resistance, subcompensated type 2 diabetes mellitus under baseline therapy, pronounced atherogenic dyslipidemia, and biochemical signs of cytolytic syndrome. Utilizing quantitative ultrasound fat fraction (UDFF) and shear wave elastography (pSWE), moderate liver steatosis was diagnosed in the absence of significant fibrotic changes (stage F0). The form of MASLD was verified as steatohepatitis based on the persistent activity of liver enzymes over time and the exclusion of other etiological factors. Results. A detailed periodontal examination and instrumental-radiological evaluation of the dental status confirmed severe alveolar bone destruction, pronounced pathological tooth mobility, and poor oral hygiene, fulfilling the criteria for stage IV, grade C periodontitis. Given the presence of type 2 diabetes mellitus, obesity, MASLD, and critically elevated LDL levels, which stratify the patient into a very high cardiovascular risk category, high-intensity statin therapy was reasonably incorporated into the treatment regimen to achieve target lipid parameters in accordance with current cardiometabolic guidelines. Conclusions. This case emphasizes the necessity of early proactive screening for liver steatosis and fibrosis in patients with periodontitis and metabolic disorders, even at a young age. Multidisciplinary collaboration among a dentist, general practitioner, endocrinologist, and ultrasound specialist represents a fundamental prerequisite for the timely detection of MASLD and the prevention of comorbid complications.